Integrating computers into the curriculum: a development project... Computer Assisted Case Studies, or CACS. - Gwinnett A; Massie S (Nurse Education Today, 1986)
This article introduces the idea of Computer Assisted Case Studies, or CACS, which we believe to be a new approach to Computer Assisted Learning (CAL) in nurse education. CACS combines the use of seminars/discussions with accessing information via a computer terminal. This is seen as an important step towards helping nurses to develop computer awareness in preparation for the use of ward-based teminals. It outlines the first steps in a joint project undertaken by St George's and the University of Manchester Institute of Science and Technology (UMIST) to develop and pilot computer software of a more imaginative nature than is currently used in the St George's CAL unit. It gives a brief history of the project, the main aim of which is to maximise use of learning resources. Details are given of the computer facilities available to both learners and teachers. Some attempt has already been made to incorporate CAL into the curriculum at St George's, and the use of CACS is seen as a further step in that direction. It is hoped that a fuller report will be produced in the future, when further piloting and development has been undertaken.